EKSPLORASI KONSEP MATEMATIKA PADA PROSESI ADAT ISTIADAT GUNTING RAMBUT DAN TINJAK TANAH DI MATANJAYA - Kardiyono Kardiyono; Bistari Bistari; Silvia Sayu (Universitas Tanjungpura, 2020)
Abstract This research aimed to reveal the mathematical concept in the traditional procession of the Gunting Rambut and Tinjak Tanah at desa Matan Jaya. The research form used in this research was a case study. The research subjects in this research were the people at desa Matan Jaya. Data processing in this research used qualitative analysis techniques. The data analyzed was data obtained direct observation, documentation, and interviews. The research result found knowledge, preparation, and implementation of the custom procession of the Gunting Rambut and step Tinjak Tanah at the desa Matan Jaya. The data analysis result showed that the procession of the Gunting Rambut and Tinjak Tanah at desa Matan Jaya contained ethnomatematics. The mathematical concepts contained in the custom procession of the Gunting Rambut and Tinja Tanah at desa Matan Jaya was operations on integers and fractions, odd numbers, number intervals, flat shapes, spatial shapes, time, probability, combinations, sets, rows and series, and social arithmetic.Keywords: Customs of the Gunting Rambut and Tinjak Tanah, Ethnomatematics, Mathematical concepts